Mitigating Research Challenges among Post Graduate Students through Effective Library Service Delivery - Stephen Adekunle Ajayi, Uwaebuka Wisdom Madu, Modupe Aduke Aboyade & (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2019)
Postgraduate students across Nigerian universities face various challenges in their quest for higher degrees. The study adopted a survey method to examine the research challenges faced by postgraduate students in three selected universities in Osun State and the role that university libraries play in mitigating them. The selected universities are Obafemi Awolowo University Ile-Ife, Osun State University, Oshogbo and Redeemers University Ede. Structured and validated questionnaire was used as instrument for data collection. 370 copies of the questionnaire were distributed while 300 representing 81% were retrieved and found valid for analysis. The data generated for the study were analyzed using Mean and Standard deviation. Findings of the study showed that the postgraduate students are confronted with several challenges in their research activities. It equally revealed that, the libraries are not lacking in their role of offering necessary facilities/services to aid research by postgraduate students as the students showed appreciable level of satisfaction with the services being provided by their university libraries. However, inadequate electronic resources, erratic power supply, insufficient ICT facilities as well as insufficient awareness were identified as the greatest challenges hindering effective use of library services by the postgraduate students. Consequently, it was recommended that adequate funding should be provided by the parent institutions for the procurement of electronic resources, ICT facilities and functional alternative power supply. Also, user education programmes should be improved upon and extended with the postgraduate students in mind.